The effect of hydraulic retention time in municipal solid waste landfill leachate treatment using UASB reactor - Ab. Malek, M.I.; Yee, S.T.M.; Husnon, N.; Shaaban, M.G. (2008)
The treatability of municipal solid waste (MSW) landfill leachate using upflow anaerobic sludge blanket (UASB) was investigated. Leachate samples were collected from Jeram landfill and its characteristics were studied. Among the parameters concerned were the BOD5, COD, SS, pH, ammoniacal nitrogen, alkalinity (CaCO3), chloride, phosphate, and metals (sodium, magnesium, potassium, calcium, chromium, manganese, iron, nickel, copper, zinc, lead and cadmium). The BOD5/COD ratio obtained was 0.70. Leachate samples were then being treated in UASB reactor with start-up hydraulic retention time (HRT) of 36 hours for two weeks. To ensure the granular formation initiated, variables such as substrate and environmental factors were controlled accordingly to ensure optimum operating conditions. Treatment of leachate were carried out by reducing the initial HRT 36 hours by 8 hours gradually with each reduction to last for a week (36, 28, 20 and 12 hours). The effect of HRT variation in UASB system performance in leachate treatment in COD and TSS removal was then analyzed.